যদি \(\cfrac{b+c−a}{y+z−x}=\cfrac{c+a−b}{z+x−y}=\cfrac{a+b−c}{x+y−z}\) হয়, তবে প্রমাণ করো যে,\(\cfrac{a}{x}=\cfrac{b}{y}=\cfrac{c}{z}\) । Madhyamik 2019


\(\cfrac{b+c−a}{y+z−x}=\cfrac{c+a−b}{z+x−y}=\cfrac{a+b−c}{x+y−z}\)
\(=\cfrac{b+c-a+c+a-b+a+b-c}{y+z-x+z+x-y+x+y-z}\)

[সংযোজন প্রক্রিয়া করে পাই]



\(=\cfrac{a+b+c}{x+y+z}\)

\(\therefore \cfrac{b+c−a}{y+z−x}=\cfrac{a+b+c}{x+y+z}\)
\(=\cfrac{(a+b+c)-(b+c-a)}{(x+y+z)-(y+z-x)}\)
\(=\cfrac{2a}{2x}=\cfrac{a}{x}\)
\(\therefore\) প্রতিটি অনুপাত \(\cfrac{a}{x}\) এর সমান ।

আবার, \(\cfrac{c+a-b}{z+x-y}=\cfrac{a+b+c}{x+y+z}\)
\(=\cfrac{(a+b+c)-(c+a-b)}{(x+y+z)-(z+x-y)}\)
\(=\cfrac{2b}{2y}=\cfrac{b}{y}\)
\(\therefore\) প্রতিটি অনুপাত \(\cfrac{b}{y}\) এর সমান ।

এবং, \(\cfrac{a+b-c}{x+y-z}=\cfrac{a+b+c}{x+y+z}\)
\(=\cfrac{(a+b+c)-(a+b-c)}{(x+y+z)-(x+y-z)}\)
\(=\cfrac{2c}{2z}=\cfrac{c}{z}\)
\(\therefore\) প্রতিটি অনুপাত \(\cfrac{c}{z}\) এর সমান ।

\(\therefore \cfrac{a}{x}=\cfrac{b}{y}=\cfrac{c}{z}\) [প্রমাণিত]

Similar Questions